The Consciousness of Learning Grammar Communicatively Through Role Play in EFL Classroom - Siska Siska (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2017)
Consciousness is a very important aspect in the teaching and learning of Grammar in EFL Classroom.It makes students become aware not only on the form or the  language pattern, but also on the meaning and the way to use it.  For this case, this research aims to describe the use of role play as a communicative task for encouraging students’ consciousness in learning grammar. The research was done in grammar class B of 2016-2017 that consisted 35 students as the participants of this research.  The researcher did observation and interview to collect the relevant data to give the better supports in finding out what had been stated in the research’s purpose.  The finding of this research showed that role play enabled the students to study grammar communicatively.  In this case, the students  became conscious to create many sentences based on the given topic and context and then use those sentences in their role-play. In other word, the students gained both grammar competence and communicative competence. Also, the researcher found that the students showed positive attitudes during the teaching and learning grammar process by using role play.